CORPORATE SOCIAL RESPONSIBILITY PROGRAM AS A CORPORATE IMPRESSION MANAGEMENT STRATEGY - Tine Silvana Rachmawati (Metakom, 2019)
This study aims to determine the public relations (PR) activities of a company, where the demands and obligations of the company in fulfilling its social and environmental responsibilities are carried out by the public relations department. The problems that will be presented in this study concerns the two factors of public relations practitioners' efforts in forming a positive image. The method used in this study is theoretical review, with the research object of PT Pertamina EP Asset 3 Subang Field. The results of this study show that the positive image of the company was identified in the usefulness and suitability of the Corporate Social Responsibility program with community needs regarding clean water, and also the community felt happy and valued because they were involved in building clean water and toilet washing facilities. Keywords: Corporate Social Responsibility; Public Relations; Impression Management.